2022
DOI: 10.25259/jcis_49_2022
|View full text |Cite
|
Sign up to set email alerts
|

A case report of mesenteric involvement in neurofibromatosis type 1

Abstract: Mutations in the Neurofibromatosis Type 1 (NF-1) gene, which is located on chromosome 17q11.2, are the cause of NF-1, an autosomal dominant hereditary condition in which tumors of the nerve system develop. Neurological, skeletal, and cutaneous abnormalities are symptoms of the condition. Of all gastrointestinal tract lesions, mesentery lesions are the least common. There are many gastrointestinal problems that can accompany mesenteric neurofibromas, or they may not. We describe a case of a 5-year-old kid with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Usually congenitally benign, PNF grows in a reticular pattern to replace normal tissue (14). PNF can be limited, nodular, or diffuse and seen in the paravertebral region of the trunk (31%), head & neck (31%) and extremities (25%) (5). Previous ultrasound reports showed that PNF was an irregularly lobulated hypoechoic mass, which ran along the nerve axis on the longitudinal image diagram and displayed target ring sign on the transverse image, with high echo in the center and low echo around.…”
Section: Local Excisionmentioning
confidence: 99%
“…Usually congenitally benign, PNF grows in a reticular pattern to replace normal tissue (14). PNF can be limited, nodular, or diffuse and seen in the paravertebral region of the trunk (31%), head & neck (31%) and extremities (25%) (5). Previous ultrasound reports showed that PNF was an irregularly lobulated hypoechoic mass, which ran along the nerve axis on the longitudinal image diagram and displayed target ring sign on the transverse image, with high echo in the center and low echo around.…”
Section: Local Excisionmentioning
confidence: 99%
“…This has no family history of NF1 and is a spontaneous mutation. CALMs are early clinical features of NF1 [ 5 ]. According to the uniform diagnostic criteria of National Institutes of Health (NIH) for NF1 in 1988, six or more CALMs are diagnostic [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Usually congenitally benign, PNF grows in a reticular pattern to replace normal tissue [ 15 ]. PNF can be limited, nodular, or diffuse and seen in the paravertebral region of the trunk (31%), head & neck (31%) and extremities (25%) [ 5 ]. Previous ultrasound reports showed that PNF was an irregularly lobulated hypoechoic mass, which ran along the nerve axis on the longitudinal image diagram and displayed target ring sign on the transverse image, with high echo in the center and low echo around.…”
Section: Introductionmentioning
confidence: 99%